Sea-Water Based Reconfigurable Reflectarray Antenna - Zainud-Deen, S. H.; Malhat, H. A.; Abdelbary, M. M. (Journal of Advanced Research in Applied Mechanics, 2020)
A high efficiency sea-water based reflectarray antenna for maritime wireless communications at 740 MHz is introduced in this paper. The proposed reflectarray consists of 169 unit-cell elements covering an area of 330.2×330.2 cm2. Each unit-cell element consists of a cylindrical dielectric container filled with sea-water mounted on conducting plate and introduces phase variation from 0 to 313 degrees. The reflectarray is designed and analyzed using the finite integral technique and compared to that calculated using the finite element method. The radiation characteristics of 13×13 sea-water based reflectarray are investigated and presented. The main beam direction of the sea-water based reflectarray is controlled by the water level in each unit-cell element through an electronic valves. The reflectarray introduces maximum gain of 26.2 dB at 740 MHz with 1-dB gain bandwidth of 50 MHz The effect of temperature variation on the electrical properties of sea-water and the radiation characteristics of the water-based reflectarray are depicted.